The effect of voluntary disclosure, foreign ownership and institutional ownership on long term debt in coal mining sub-sector companies listed on the Indonesia stock exchange - Al Hatul Julianti; Rizky Yudaruddin (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study aims to analyze the effect of voluntary disclosure, foreign ownership, and institutional ownership  on long derm debt  in coal mining sub-sector companies  listed on the Indonesia Stock Exchange. Using  the purposive sampling method, 18 companies were obtained as research samples with 2016 to 2018 used as the research period. The analysis method used is to use panel data regression analysis assisted by using statistical analysis tools, namely Eviews. The results showed that: (1) voluntary disclosure has a negative and significant effect  on long derm debt in coal mining companies listed on the Indonesia Stock Exchange. (2) foreign ownership has a negative and significant effect  on long derm debt in coal mining companies listed on the Indonesia Stock Exchange. (3) institutional ownership has a positive and insignificant effect  on long derm debt in coal mining companies listed on the Indonesia Stock Exchange.